Implementing the Jigsaw Method to Strengthen Learning Outcomes in Islamic Religious Education - Leni Anggraini; Sanjaka Yekti (Mandalika Institute, 2026)
This study aims to analyze the implementation of the Jigsaw-type cooperative learning method in strengthening student learning outcomes in Islamic Religious Education for Grade X. A qualitative approach was employed to gain an in-depth understanding of the instructional process and students’ experiences during the application of the Jigsaw method. The research participants consisted of 124 students, including 42 male and 83 female students. Data were collected through observation, interviews, and documentation to obtain a comprehensive depiction of both the learning process and its outcomes. The findings indicate that the implementation of the Jigsaw method enhances student activeness, engagement, and comprehension of Islamic Religious Education materials. Students become more actively involved in discussions, develop a stronger sense of responsibility for the material being studied, and demonstrate improved collaboration within groups. Furthermore, this method fosters a more interactive and enjoyable learning environment, which contributes to the strengthening of student learning outcomes. Therefore, the Jigsaw-type cooperative learning method can serve as an effective alternative for improving the quality of Islamic Religious Education. This study is expected to provide a valuable reference for teachers in developing innovative, student-centered instructional strategies.